Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Consider the equation:
0 = x^2 - 10x + 10
1) Rewrite the equation by completing the square.
Your equation should look like (x + a)2 = b or (x - c)2 = d.



Sagot :

DWRead
x² - 10x + 10 = 0

Isolate the constant term

x² - 10x = -10

Complete the square
• coefficient of the x term: -10
• divide in half: -5
• square it: (-5)² = 5²
• add 5² to both sides, to complete the square and keep the equation balanced:
x² - 10x + 5² = -10 + 5²
(x-5)² = 15

Answer:

1) We can rewrite the equation as 15=(x-5)^2

2) The solutions to the equation are x=5±15